Feedback in W49A diagnosed with radio recombination lines and models - Rugel, Michael; Rahner, Daniel; Pellegrini, Eric William; Henning, Thomas; Klessen, Ralf S.; Glover, Simon (Astronomy and astrophysics, 2019)
We present images of radio recombination lines (RRLs) at wavelengths around 17 cm from the star-forming region W49A to determine the kinematics of ionized gas in the THOR survey (The H I/OH/Recombination line survey of the inner Milky Way) at an angular resolution of 16.′′8 × 13.′′8. The distribution of ionized gas appears to be affected by feedback processes from the star clusters in W49A. The velocity structure of the RRLs shows a complex behavior with respect to the molecular gas. We find a shell-like distribution of ionized gas as traced by RRL emission surrounding the central cluster of OB stars in W49A. We describe the evolution of the shell with the recent feedback model code WARPFIELD that includes the important physical processes and has previously been applied to the 30 Doradus region in the Large Magellanic Cloud. The cloud structure and dynamics of W49A are in agreement with a feedback-driven shell that is re-collapsing. The shell may have triggered star formation in other parts of W49A. We suggest that W49A is a potential candidate for star formation regulated by feedback-driven and re-collapsing shells.